The Relationships in the Process of Knowledge Transfer According to the Triple Helix Model (European Journal of Marketing and Economics, 2025)
One of the most important challenges facing modern scientific entities is network cooperation with other organizations and a dialogue facilitating their access to information and knowledge. The essence of this relationship is well illustrated by the Triple Helix Model, which refers to network cooperation in the process of creating knowledge between the academic sector, industry and government. The aim of the study is to analyse and evaluate the relationships in the process of knowledge transfer between the academic sector and other entities working for knowledge-based economy according to the Triple Helix Model. To achieve the purpose of the work, the author used desk research and empirical research. The empirical part of the paper is a case study describing the project called V4mula, as well as conclusions from the realized qualitative research (diagnostic survey method). Project V4mula was mplemented in the network of four partners operating in the Visegrad Group.
Keywords: knowledge transfer, network cooperation, innovative processes, Triple Helix Model